Co-producing research with communities: emotions in community research. Issue 1 (1st January 2020) - Brown, Milton; Pahl, Kate; Rasool, Zanib; Ward, Paul
Abstract : In this article we explore the ways in which universities and communities can work together drawing on our experience of a community-university co-produced project called 'Imagine'. We reflect on our different experiences of working together and affectively co-produce the article, drawing on a conversation we held together. We locate our discussion within the projects we worked on. We look at the experiences of working across community and university and affectively explore these. We explore the following key questions: How do we work with complexity and difference?Who holds the power in research?What kinds of methods surface hidden voices?How can we co-create equitable research spaces together?What did working together feel like? Our co-writing process surfaces some of these tensions and difficulties as we struggle to place our voices into an academic article. We surface more of our own tensions and voices and this has become one of the dominant experiences of doing co-produced research. We explore the mechanisms of co-production as being both a process of fusion but also its affective qualities. Our discussions show that community partners working with academics have to bear the emotional labour; by 'standing in the gap' they are having to move between community and university. We also recognise the power of community co-writing as a form that can open up an opportunity to speak differently, outside the constraining spaces of academia.